Sistema de classificação facetada para café (coffea sp.) - Maya-Montalvo, Luis Alejandro (1983)
The objetive os this work is construction, using the analytical-sunthetic method, of a faceted classification sheme for literature about and related to COFFEE This presented a bibliographical revision about the theory of the classification of knowledge, about faceted classification, about the concepts and their fundamental relationships, about the principles of division and citation order, about categories, facets, subfacets, notations and indexes By means of the analytical-synthetical method, the existent concepts in approximately 15.000 titles and summaries of documents concerning COFFEE are analized. With the application of diverses principles of integration, and order is established in the concepts within the groups Following in part the model of "Classification Research Group-GRG" and in part the model of Vickery, the concepts in the following categories are grouped together in this order of citation: Whole/Types/Parts; Products and Subproducts; Constituents; Properties; Processes; Operations; Ahents; Supplies and Tools; Space; Time; Commons Attributes and Subdivisions of Form The principal classes of the subject are referred to categories, and the groups and subgroups within the Categories as Facets and Subfacets A mixed notation is used numbers for the categories, capital letters for the facets and small letters for the subfacets. Concepts corresponding to geographical space are represented by arabic numbers in parentheses; time is indicated by the numbers corresponding to the year and common attributes and subdivisions of form are symbolized by to small letters preceded by two points An alphabetical index of the concepts of the scheme is presented. The application is demonstrated classifying 10 documents chosen from the bibliographies of the subject.